THE EFFECT OF ANDROID-BASED SEXUALITY EDUCATION APPLICATION ON ADOLESCENT KNOWLEDGE ABOUT SEXUALITY - Natosba, Jum; Azizah, Nida; Wahyuni, Dian (Journal of Maternity Care and Reproductive Health, 2025)
Adolescence is a period where rapid growth and development occurs both physically, psychologically and intellectually. The typical characteristic of teenagers is that they have a great sense of curiosity, like adventure and challenges and tend to be brave enough to take risks in their actions without prior careful consideration. If a decision taken in dealing with a problem or conflict is not appropriate, then they will fall into risky behavior and may have to bear the short-term and long-term consequences of various physical and psychosocial health problems. The nature and risky behavior of adolescents requires the availability of caring adolescent health services that can meet the health needs of adolescents, including services for reproductive health. This research aims to explain and analyze the influence of the Sexuality Education Application on knowledge about adolescent sexuality. This type of research is quantitative research using the alternative Wilcoxon test for the intervention group and the Paired Samples t test for the control group. The population in this study was 4713 Unsri Indralaya students, so the sample taken was 448 respondents. Based on the research results, it was found that the p value was 0.000 or <0.05, which means there was a significant difference between knowledge of sexuality in adolescents before and after using the Sexuality Education Application in the intervention group, while in the control group the p value was 0.524 (α <0.05). which means that there is no significant difference between knowledge of sexuality in adolescents in the first and second measurements. This means that there is an influence of sex education using the Sexuality Education Application on increasing knowledge about sexuality in teenagers. Sexuality education through the Sexuality Education Application can increase knowledge and information about the importance of reproductive health and knowledge about sexuality in adolescents.